Dampak Sosial Ekonomi Pedagang Terdampak Relokasi Pasar Godean ke Tempat Penampungan Sementara - Sugiyanto (Universitas Bojonegoro, 2024)
The revitalization efforts of Godean Market require its traders to relocate to Temporary Shelters (TPS). The large number of traders in Godean Market means that the traders are relocated to three TPS locations, two of which are: in Sidokarto and Hobbies Market. However, conflict occurs when traders are dissatisfied with the relocation policy to the three TPS. The approach used in this study is qualitative with a case study method. The case study referred to in this study is the socio-economic impact on traders affected by the revitalization of Godean Market in two study locations. The results of the research found in the field, the response of traders to the relocation policy of Godean Market to two Temporary Shelters (TPS) locations, Sidokarto Market and Hobbies Market, is classified as less than satisfactory. This is due to minimal facilities and not being made in one area. The socio-economic impact of the TPS is that the relationship between fellow traders is closer and closer than before. Another impact is that traders feel that there is a change in place/plot that is different from before which was so narrow and uncomfortable. This is because the government divides places/plots based on the zoning system. There are public facilities that have been damaged but have not been repaired. Public facilities provided by the local government in both TPS are free but some are paid. Traders who want a place must pay a comfort fee. The change in trading location has decreased the income of traders by 30%-70%. However, traders are learning to utilize technology by selling online so that they can earn income of up to 20-25%